Optimalisasi Edukasi Metode Brainstorming untuk Meningkatkan Self Care Management pada Pasien Hipertensi - nurarifah; Sukmawati, Sukmawati; nurarifah, nurarifah (Jurnal Pengabdian Kepada Masyarakat Citra Delima, 2024)
Hypertension is a non-communicable disease with a prevalence that continues to increase every year. The problem that occurs in society is a lack of understanding about self-care management, which causes uncontrolled blood pressure and the risk of lasting complications such as stroke. Education aims to increase knowledge about the benefits and obstacles and self-care management efforts in controlling blood pressure. The community service methods used are health checks, providing modules and brainstorming-based education about self-care management for hypertension patients. The evaluation results obtained were that before education was carried out using the brainstorming method, only 13 participants (37%) had a good level of knowledge about self-care management and this increased to 31 participants (89%). Participants very enthusiastically expressed the opinion that it is very important to check blood pressure every month and change lifestyle and behavior patterns. It is hoped that counseling will be carried out on a scheduled basis so as to increase knowledge and self-care management of hypertension patients.